Програмні та апаратні засоби створення прямої трансляції - Дорофєєв, Д. О. (ХНУРЕ, 2023)
Software and hardware tools were used in the course of the work, such as OBS, vMix, Wirecast, XSplit, as well as cameras, codecs, servers, routers and switches to create a live stream. I have analyzed the advantages and disadvantages of the main varieties of live streaming methods
Keywords: пряма трансляція